Genomic Analysis of Soybean PP2A-B′′ Family and Its Effects on Drought and Salt Tolerance - Xiong, Yang; Fan, Xu-Hong; Wang, Qiang; Yin, Zheng-Gong; Sheng, Xue-Wen; Chen, Jun; Zhou, Yong-Bin; Chen, Ming; Ma, You-Zhi; Ma, Jian; Xu, Zhao-Shi (Frontiers in Plant Science, 2022)
Abiotic stresses induce the accumulation of reactive oxygen species (ROS) and significantly affect plant growth. Protein phosphatase 2A (PP2A) plays an important role in controlling intracellular and extracellular ROS signals. However, the interaction between PP2A, ROS, and stress tolerance remains largely unclear. In this study, we found that the PP2A-B" subunit can be significantly induced and was analyzed using drought- and salt-induced soybean transcriptome data. Eighty-three soybean PP2A-B" genes were identified from the soybean genome via homologous sequence alignment, which was distributed across 20 soybean chromosomes. Among soybean PP2A-B" family genes, 26 GmPP2A-B" members were found to be responsive to drought and salt stresses in soybean transcriptome data. qPCR analysis demonstrated that GmPP2A-B"71 had the highest expression levels under salt and drought stresses. Functional analysis demonstrated that overexpression of GmPP2A-B"71 in soybeans can improve plant tolerance to drought and salt stresses; however, the interference of GmPP2A-B"71 in soybean increased the sensibility to drought and salt stresses. Further analysis demonstrated that overexpression of GmPP2A-B"71 in soybean could enhance the expression levels of stress-responsive genes, particularly genes associated with ROS elimination. These results indicate that PP2A-B" can promote plant stress tolerance by regulating the ROS pathway, which will contribute to improving the drought resistance of crops.